Depth of discharge characteristics and control strategy to optimize electric vehicle battery life. (March 2023) - Park, Sang-Jun; Song, Young-Woong; Kang, Byeong-Su; Kim, Woo-Joong; Choi, Yeong-Jun; Kim, Chanhoon; Hong, Young-Sun
Abstract: To comply with the global low-carbon green growth policy, the automobile industry is rapidly shifting from internal combustion engine to electric vehicles, which use high-Ni cathode active materials with high energy density, because mileage per charge is prioritized by the user. However, the high-Ni active material presents poor cycle characteristics because impurities generated by cation mixing increase the resistance and are also structurally unstable. Accordingly, the energy efficiency and safety of the battery were improved in this study by controlling the depth of discharge (DOD) in accordance with the state of health (SOH) of the battery. The charge/discharge characteristics and deterioration factors of 18, 650 cylindrical batteries were investigated based on the set DOD conditions. The optimal DOD was set by analyzing the total discharge energy up to the end of life of the battery, Coulombic efficiency, internal resistance, Li plating, and the state of the positive electrode active material. Considering the optimal DOD setting conditions corresponding to the battery condition, DOD70 at 100–90 % SOH and DOD60 at 90–80 % SOH were found to be the most effective in terms of cycle characteristics and safety. The optimal DOD control method increased the total discharge energy by approximately 45 % relative to DOD60. Highlights: Electric vehicles require battery packs providing high mileage per charge. The High‑nickel cathode active material has poor cycle characteristics. Depth of discharge (DOD) is used to improve battery performance and life. We optimized the DOD based on the state of health of the battery. The cycle characteristics and safety are improved under the optimized DOD.